Perancangan dan Analisa Sistem Pengelolaan Data Kepegawaian Di PT. Telesindo Shop Makassar - Hiuwono, Christoforus S.N.P (TEMATIKA, Journal of Informatics and Information Systems, 2018)
Resign level employee at PT. Telesindo Shop Makassar increased to 10,87%, which means that turnover rate at PT. Telesindo Shop Makassar was high. The high employee turnover rate affected selling performance at PT. Telesindo Shop Makassar became unstable. This research is using interview dan questionnaire method in taking data and using likert scale method in data management. Base on the research, the employee job satisfaction level in Telesindo is divided into five job satisfaction variables the first one is the work itself has an employee satisfaction score 22,06%, the boss variable has an emplyee satisfaction score 19,58%, the coworker’s variable has 22,37%, tha promotion variable has 17,71% and the salary variable has 18,29% score of employee satisfaction. The result of all the percentages can be concluded that the value of empoyee job satisfaction in Telesindo is base on the promotional variable that working there. Finally, this research is expected to be the consideration to the leader of PT. Telesindo Shop Makassar to improving emplyee’s job satisfaction so that will help to stabilize the selling performance.Keywords: Employees, Job Satisfaction, Indicator, Selling Performance, Variable.